2021
DOI: 10.5009/gnl20288
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Guidelines for the Treatment of <i>Helicobacter pylori</i> Infection in Korea 2020

Abstract: Helicobacter pylori infection is one of the most common infectious diseases worldwide. Although the prevalence of H. pylori is gradually decreasing, approximately half of the world's population still becomes infected with this disease. H. pylori is responsible for substantial gastrointestinal morbidity worldwide, with a high disease burden. It is the most common cause of gastric and duodenal ulcers and gastric cancer. Since the revision of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
120
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(122 citation statements)
references
References 202 publications
0
120
0
2
Order By: Relevance
“…Another study from 2006 to 2015 reported a similar result [ 21 ], but the number of subjects was relatively small (231 subjects). Interestingly, although there is a difference in the rate of antibiotic resistance in various geographic areas, BQT shows successful results and is recommended as a first- or second-line therapy in most areas [ 5 , 6 , 7 , 8 , 9 , 22 ]. Recent European data (Hp-EuReg) also showed similar results to this study in second-line BQT [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another study from 2006 to 2015 reported a similar result [ 21 ], but the number of subjects was relatively small (231 subjects). Interestingly, although there is a difference in the rate of antibiotic resistance in various geographic areas, BQT shows successful results and is recommended as a first- or second-line therapy in most areas [ 5 , 6 , 7 , 8 , 9 , 22 ]. Recent European data (Hp-EuReg) also showed similar results to this study in second-line BQT [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 2013 Korean guideline recommends a duration of approximately 7 to 14 days for second-line BQT [ 7 ]. The more recently published 2020 Korean guideline recommends BQT for 14 days as a second-line therapy [ 8 ], but this recommendation has not yet been widely accepted in clinical settings. Considering the potential for adverse events and difficulties with compliance, some clinicians prefer a 7-day regimen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In China, primary resistance rate to clarithromycin was 20-50% [24]. The resistance rate of clarithromycin in Korea was 17.8-31.0% [25], and the clarithromycin resistance rate in Japan was 38.5% [26]. Resistance to clarithromycin was significantly associated with failure of clarithromycin-containing regimens.…”
Section: Challenges Of H Pylori Management and Recommended Detecting Strategymentioning
confidence: 98%